Flat plate type solid oxide oxygen ion conductor membrane reactor, preparation method and application
Through the electrochemical driving of the flat-plate solid oxide oxygen ion conductor film reactor, the composite electrode of LSGM and BSCF-SDC materials is used to solve the shortcomings of the existing argon purification methods, and the high purification of argon and deep removal of trace oxygen are achieved, which is suitable for the preparation of high-purity argon.
Patent Information
- Application Number
- CN202510299609.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The existing argon purification methods have huge equipment, high energy consumption, and are difficult to meet the needs of deep separation of trace oxygen, and may introduce new impurities, affecting the purity of argon.
The flat-plate solid oxide oxygen ion conductor film reactor is used to drive selective migration of oxygen ions by electrochemically, and the composite electrode of LSGM and BSCF-SDC materials is used to achieve deep removal of trace oxygen in argon.
It has achieved high purification of argon, oxygen concentration is less than 10 ppm, and has the advantages of high energy conversion efficiency, cleanliness and continuous operation. It is suitable for semiconductor manufacturing, metal smelting and photovoltaic material processing.
Smart Images

Figure CN120079207A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical gas separation and purification, and specifically relates to a flat-plate solid oxide oxygen ion conductor membrane reactor, a preparation method and an application thereof, specifically to a method for highly purifying argon, and is particularly suitable for removing trace oxygen impurities. Background Art
[0002] As an inert gas, argon has a wide range of applications in many fields such as metal smelting, semiconductor manufacturing, photovoltaic material processing and scientific research experiments. With the development of various industries, the requirement for the purity of argon is continuously increasing. Especially in some high-end application scenarios, such as the manufacture of ultra-large scale integrated circuits, ultra-high purity argon (oxygen content ≤ 10 ppm) is required, and the presence of trace impurities may have a serious impact on the product quality. Trace oxygen impurities in argon are one of the key factors affecting the purity of argon. However, there are many deficiencies in traditional argon purification methods.
[0003] Although the cryogenic distillation method can achieve a certain degree of argon-oxygen separation, this method has large equipment, relies on liquid nitrogen cooling with high energy consumption, and has limited effect on the deep removal of trace oxygen; the adsorption method is relatively simple to operate, but the adsorption capacity of the adsorbent is limited, requires frequent regeneration, and is difficult to meet the demand for deep separation of trace oxygen. In addition, the chemical absorption method may introduce new impurities during the process of absorbing oxygen, which is likely to have a negative impact on the purity of argon. Therefore, it is of great practical significance to develop a purification method that is efficient, energy-saving, can operate continuously and can deeply remove trace oxygen in argon.
[0004] A typical prior art such as "Design of an industrial multi-bed (V)PSA unit for argon concentration" (Separation and Puriffcation Technology 261 (2021) 118254) proposes that a pressure swing adsorption system has been designed for enriching argon from a binary mixed gas of oxygen and argon ( O 2 : Ar =95:5 molar percentage) generated from an industrial oxygen production vacuum pressure swing adsorption (VSA) device in air. A single vacuum pressure swing adsorption unit cannot enrich argon to a purity of more than 98%, and this purity is usually required in some applications, such as steel production and inert gas welding. Therefore, a second vacuum pressure swing adsorption unit is added to further improve the purity of argon, and it is found that the integrated two-stage vacuum pressure swing adsorption system can achieve the following overall performance: argon purity is 98.1%, argon recovery rate is 20.3%, and the productivity of the adsorption bed is 0.011 molAr . kgads −1 h −1 , the specific energy consumption is 53.2 MJ / kg Ar −1 . Considering the actual efficiency of turbomachinery, the energy consumption ratio of the proposed vacuum pressure swing adsorption unit is 75% higher than that of the traditional independent cryogenic distillation system designed to achieve the same separation effect.
[0005] The solid oxide oxygen ion conductor membrane reactor technology can theoretically achieve efficient and continuous deoxidation through the electrochemically driven selective migration of oxygen ions, and has good application prospects in the field of gas separation and purification. Summary of the Invention
[0006] To solve the disadvantages and deficiencies of the prior art, the present invention provides a flat solid oxide oxygen ion conductor membrane reactor, a preparation method of the flat solid oxide oxygen ion conductor membrane reactor, an oxygen-argon separation method using the flat solid oxide oxygen ion conductor membrane reactor, and an application of the flat solid oxide oxygen ion conductor membrane reactor.
[0007] In the first aspect, the present application proposes a flat solid oxide oxygen ion conductor membrane reactor. Specifically, to achieve the above object, the present invention is implemented by at least one of the following technical solutions.
[0008] The flat solid oxide oxygen ion conductor membrane reactor provided by the present invention includes an anode and a cathode, as well as a wire and a power source, and the anode and the cathode are connected to the power source through the wire; The anode and the cathode include a support body, and cathode and anode coatings on both sides of the support body. The support body is an LSGM sheet, and the coating is a layer formed by coating BSCF-SDC slurry.
[0009] The LSGM is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ .
[0010] The BSCF is Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ .
[0011] The SDC is Ce 0.8 Sm 0.2 O 2-δ .
[0012] The BSCF-SDC is a material obtained by co-calcining BSCF and SDC.
[0013] Further, the wire is a silver wire.
[0014] Further, the power supply voltage is 1 - 2.0 V, preferably 1.2 - 1.5 V.
[0015] Further, the support of the membrane reactor is selected from one of the oxygen ion conductive electrolytes, preferably LSGM.
[0016] In a second aspect, the present application provides a method for preparing a flat - type solid oxide oxygen ion conductor membrane reactor as in the first aspect, comprising the following steps: (1) Preparing the support of the solid oxide membrane reactor; (2) Preparing the anode and cathode materials of the solid oxide membrane reactor; (3) Coating the anode material and the cathode material on both sides of the support respectively; (4) Heat - treating the anode and cathode at 1000 - 1200 °C for 3 - 10 hours, then coating a current - collecting layer on both sides, and fixing wires on both sides of the composite cathode and the composite anode to obtain a standby membrane reactor.
[0017] Specifically, for (1), forming the LSGM precursor powder into sheets and heat - treating at 1400 - 1500 °C as the support and electrolyte of the membrane reactor; (2) Mixing and sintering BSCF and SDC in a mass ratio of 3:1 - 1:1, adding 10 - 20% of ethyl cellulose, 3 - 5% of starch and turpentine alcohol based on the total mass of BSCF - SDC after sintering, and mixing and ball - milling to prepare a BSCF - SDC slurry; (3) Coating the BSCF - SDC slurry obtained in step (2) on both sides of the LSGM support as the composite cathode and anode of the membrane reactor; (4) After coating the BSCF - SDC slurry, heat - treating at 900 - 1200 °C; coating silver paste on the surfaces of the anode and cathode, and then sticking wires on the silver paste surfaces to obtain a membrane reactor for separating trace oxygen in argon; The LSGM is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ ; The BSCF is Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ ; SDC is Ce0.8 Sm 0.2 O 2-δ ; The BSCF-SDC is a material obtained by co-calcining BSCF and SDC.
[0018] Further, in step (1), the heat treatment time at 1400-1500 °C is 8-20 hours, preferably 10-15 hours.
[0019] Further, in step (4), the heat treatment time at 900-1200 °C is 1-20 hours, preferably 2-10 hours, more preferably 2-6 hours.
[0020] Further, the LSGM is prepared by the following method: (a) Weigh La 2 O 3 , SrCO 3 , Ga 2 O 3 , and MgO according to the stoichiometric ratio, grind them evenly, and the grinding time is 10-50 hours, preferably 20-30 hours; during the grinding process, add ethanol or acetone, and the total amount of La 2 O 3 , SrCO 3 , Ga 2 O 3 , and MgO and the organic solvent is in the ratio of 1 g: 0.5-2 mL, preferably 1 g: 0.5-1.5 mL; Further, the rotation speed of the grinding is 300-1000 r / min, preferably 300-500 r / min.
[0021] (b) Dry the evenly ground powder and calcine it at 800-1200 °C for 4-12 hours, preferably calcine it at 900-1000 °C for 6-8 hours to obtain LSGM precursor powder; Further, the calcination is carried out in an oxygen-containing atmosphere, preferably in an air atmosphere.
[0022] Further, the heating rate of the calcination is 1-5 °C / min, preferably 1-2 °C / min.
[0023] (c) Use a tablet press to press the LSGM precursor powder into a round sheet, and heat-treat it at 1400-1500 °C for 8-20 hours, preferably 10-15 hours, as the support and electrolyte of the membrane reactor.
[0024] In a third aspect, the present application also provides an oxygen-argon separation method using the flat solid oxide oxygen ion conductor membrane reactor of the first aspect.
[0025] Further, fix the membrane reactor in a mold. At a temperature of 750 - 900 °C, introduce an argon-oxygen mixture to the cathode side of the membrane reactor and purge with helium on the anode side; apply an electrolysis voltage of 1 - 2.0 V, preferably 1.2 - 1.5 V, between the composite anode and the composite cathode.
[0026] Further, an argon-oxygen mixture is introduced to the cathode side of the membrane reactor, and the oxygen concentration is 0.1 - 5%; preferably, the oxygen concentration is 0.5 - 1%.
[0027] An argon-oxygen mixture with a flow rate of 3 - 10 mL / min is introduced to the cathode of the membrane reactor; preferably 3 - 5 mL / min; Nitrogen or helium with a flow rate of 40 - 80 mL / min is introduced to the anode of the membrane reactor, preferably 50 - 60 mL / min.
[0028] Further, the oxygen concentration of the purified argon is less than 10 ppm.
[0029] Further, the applied voltage of the membrane reactor is 1 - 2.0 V, and the oxygen ions obtained from the cathode pass through the electrolyte of the membrane reactor to reach the anode side.
[0030] The operating temperature of the membrane reactor is 750 - 900 °C.
[0031] Further, the upper limit of the temperature is 900 °C, 850 °C or 800 °C; the lower limit is selected from 850 °C, 800 °C or 750 °C.
[0032] Further, the method for highly purifying argon by the membrane reactor is to compound the catalyst BSCF with SDC, thereby reducing the thermal expansion coefficient of BSCF and making it combine tightly with the ceramic material substrate LSGM, which is beneficial to the continuous transmission of oxygen ions.
[0033] Further, SDC provides higher oxygen ion conductivity, and the formed nanoparticles are uniformly distributed on the surface of BSCF, effectively expanding the three-phase reaction boundary.
[0034] Further, the upper limit of the voltage is selected from 1.5 V, 1.6 V, 1.7 V, 1.8 V, 1.9 V, 2.0 V; the lower limit is selected from 1 V, 1.1 V, 1.2 V, 1.3 V, 1.4 V.
[0035] Further, the voltage between the cathode and the anode of the membrane reactor is 1 - 2.0 V. Preferably, the voltage between the cathode and the anode of the membrane reactor is 1.2 - 1.5 V.
[0036] Fourthly, the present application provides an application of a flat solid oxide oxygen ion conductor membrane reactor for oxygen-argon separation.
[0037] Further, the oxygen concentration in the argon is less than 10 ppm after purification.
[0038] Further, the membrane reactor is arranged on a membrane reactor carrier. The membrane reactor carrier includes a reactor tube body. A first three-way pipe is arranged at the upper part of the reactor tube body. One end of the first three-way pipe is connected to an inlet pipe for the gas to be purified, one end is connected to an outlet pipe for the purified gas, and one end is connected to the reactor tube body. A second three-way pipe is arranged at the lower part of the reactor tube body. One end of the second three-way pipe is connected to a purge gas inlet pipe, one end is connected to a purge gas outlet pipe, and one end is connected to the reactor tube body.
[0039] Further, the membrane reactor carrier is placed in a heat source to provide a reaction temperature atmosphere. Specifically, the heat source can be a furnace such as a tube furnace or a muffle furnace.
[0040] The beneficial effects that the present application can produce include: 1) For the argon highly purification method based on a membrane reactor provided by the present application, SDC nanoparticles are introduced into the electrodes of the membrane reactor, which improves the oxygen ion conductivity of the electrodes, enhances the thermo-mechanical matching degree between the electrodes and the electrolyte, and also expands the three-phase boundary of the reaction; 2) The argon highly purification method based on a membrane reactor provided by the present application can operate continuously and has good long-term stability; 3) The argon highly purification method based on a membrane reactor provided by the present application can deeply remove trace oxygen in argon, make the oxygen concentration in argon less than 10 ppm, and the purified argon can be directly used in fields such as semiconductor manufacturing, metal smelting, and photovoltaic material processing; 4) The argon highly purification method based on a membrane reactor provided by the present application has the advantages of high energy conversion efficiency, cleanness, and continuous operation, and can be directly used for the preparation of high-purity argon. Description of the Drawings
[0041] Figure 1 (a) is an in-situ X-ray diffraction pattern of BSCF-SDC electrode material from room temperature to 800 °C, Figure 1 (b) is an enlarged view of its main peak at 30-33°; Figure 1 (c) is an in-situ X-ray diffraction pattern of BSCF electrode material from room temperature to 800 °C, Figure 1 (d) is an enlarged view of its main peak at 30-33°.
[0042] Figure 2 (a) is a scanning electron microscope image of the cross-section of a BSCF-SDC / LSGM / BSCF-SDC membrane reactor;Figure 2 (b) is the scanning electron microscope image of the BSCF-SDC porous electrode; Figure 2 (c) is the particle size statistical chart of SDC nanoparticles.
[0043] Figure 3 (a) is the scanning electron microscope image of the cross-section of the BSCF / LSGM / BSCF membrane reactor; Figure 3 (b) is the scanning electron microscope image of the BSCF porous electrode; Figure 4 is the oxygen permeation performance diagram of the BSCF / LSGM / BSCF membrane reactor and the BSCF-SDC / LSGM / BSCF-SDC membrane reactor at 600 - 800 °C, with the feed gas being air at 50 mL / min and an external applied voltage of 1.2 V.
[0044] Figure 5 (a) is the current density and Faraday efficiency of the BSCF-SDC / LSGM / BSCF-SDC membrane reactor at 600 - 800 °C, with the feed gas being an oxygen-argon mixture with an oxygen concentration of 0.5% and a flow rate of 3 mL / min, and an external applied voltage of 1.2 V.
[0045] Figure 5 (b) is the oxygen permeation amount and argon purification rate of the BSCF-SDC / LSGM / BSCF-SDC membrane reactor at 600 - 800 °C, with the feed gas being an oxygen-argon mixture with an oxygen concentration of 0.5% and a flow rate of 3 mL / min, and an external applied voltage of 1.2 V.
[0046] Figure 6 is the schematic diagram of the membrane reactor support.
[0047] The labels in the figure are: 100, membrane reactor support; 1, inlet pipe for the gas to be purified; 2, outlet pipe for the purified gas; 3, heat source; 4, reactor tube body; 5, outlet pipe for the purge gas; 6, inlet pipe for the purge gas; 11, first three-way pipe; 12, second three-way pipe. Specific implementation manners
[0048] The present application will be described in detail below in conjunction with the embodiments, but the present application is not limited to these embodiments. The raw materials in the embodiments of the present application can all be purchased through commercial channels.
[0049] The drugs and preparation methods required for preparing materials such as LSGM, SDC, and BSCF used in the embodiments are as follows: Shanghai Macklin Biochemical Co., Ltd.: MgO (purity ≥ 98.5%), Ce(NO 3 ) 3 ·6H 2 O (purity ≥ 99.0%), Sm(NO3 ) 3 ·6H 2 O (purity ≥ 99.0%), Ba(NO 3 ) 2 (purity ≥ 99.5%), Sr(NO 3 ) 2 (purity ≥ 99.5%), NH 4 ·OH (purity 25 - 28%), HNO 3 (purity 65 - 68%).
[0050] Shanghai Aladdin Biochemical Technology Co., Ltd.: La 2 O 3 (purity ≥ 99.90%), Ga 2 O 3 (purity ≥ 99.999%), SrCO 3 (purity ≥ 99.0%), Co(NO 3 ) 3 6H 2 O (purity ≥ 99.0%), Fe(NO 3 ) 3 ·9H 2 O (purity ≥ 99.0%), glycine (purity ≥ 99.5%), EDTA (purity ≥ 99.50%), anhydrous citric acid (purity ≥ 99.50%).
[0051] Sinopharm Chemical Reagent Co., Ltd.: silver wire (0.2 mm).
[0052] Shanghai Xinlu Electronic Materials Co., Ltd.: silver paste.
[0053] La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) was prepared by solid - state synthesis method according to the literature (Xiuli H, Kui X. Active and stableNi / Cr 2 O 3-δ cathodes for high temperature CO 2 electrolysis. Journal of PowerSources. 2019; 430; 20–24).
[0054] Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O3-δ (BSCF) was prepared by the sol-gel method according to the literature (Zhenbao Z, Wulan Z, Ziwei Y, Jiahui J, Dengjie C, Zongping S. Enabling efficient hydrogen-evolution reaction over perovskite oxide electrocatalysts through phosphorus promotion. International Journal of Hydrogen Energy. 2020; 45; 24859-24869).
[0055] Ce 0.8 Sm 0.2 O 2-δ (SDC) was prepared by the solution combustion method according to the literature (Lingting Y, Changchang P, Minyi Z, Chunsen L, Fanglin C, Lizhen G, and Kui X. Highly efficient CO 2 electrolysis on cathodes with exsolved alkaline earth oxide nanostructures. ACS APPLIED MATERIALS & INTERFACES. 2017; 30; 25350-25357).
[0056] To enable those skilled in the art to conduct relevant repeated experiments, the above-mentioned literatures are all cited in this application.
[0057] In this application, the self-made device is the membrane reactor carrier 100. It includes a reactor tube body 4. A first three-way pipe 11 is arranged at the upper part of the reactor tube body 4. One end of the first three-way pipe 11 is connected to the gas inlet pipe 1 to be purified, one end is connected to the purified gas discharge pipe 2, and one end is connected to the reactor tube body 4; A second three-way pipe 12 is arranged at the lower part of the reactor tube body 4. One end of the second three-way pipe 12 is connected to the purge gas inlet pipe 6, one end is connected to the purge gas discharge pipe 5, and one end is connected to the reactor tube body 4.
[0058] Further, the membrane reactor carrier 100 is placed in a heat source 3 to provide a reaction temperature atmosphere. Specifically, the heat source 3 can be a kiln furnace such as a tube furnace or a muffle furnace. Example 1
[0059] This example is carried out according to the following steps: (1) The La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) precursor powder was pressed into a disk using a tablet press and heat-treated at 1500 °C for 10 hours to prepare a dense electrolyte with a thickness of about 400 microns, which served as the support and electrolyte of the membrane reactor.
[0060] (2) The Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) powder prepared by the sol-gel method and the Ce 0.8 Sm 0.2 O 2-δ (SDC) powder prepared by the liquid-phase combustion method were mixed in a mass ratio of 7:3 and calcined. As shown in Figure 1 (a), the in-situ XRD pattern of the calcined BSCF-SDC shows that the material always maintains consistent phase characteristics during the heating process, proving that there are no adverse reactions after the two-phase sintering composite, and no impurity phases are seen, indicating that the material has a stable structure at high temperatures. Figure 1 (b) shows that the main peak of BSCF hardly shifts in position with the increase of temperature, indicating that its lattice expansion is effectively inhibited after being compounded with SDC.
[0061] (3) Ethyl cellulose accounting for 20% of the total mass of BSCF and SDC, 5% starch, and an appropriate amount of turpentine alcohol (2 - 4 mL of turpentine alcohol is added per 1 g of the mixed mass of BSCF and SDC) were added to the composite BSCF-SDC powder, and the mixture was ball-milled for 30 hours to make a BSCF-SDC slurry. SDC has high ionic conductivity and can improve the conduction rate of oxygen ions between the cathode and the anode.
[0062] (4) The BSCF-SDC slurry was coated on both sides of the electrolyte to serve as the composite cathode and anode of the membrane reactor.
[0063] (5) After the BSCF-SDC slurry was coated, it was heat-treated in air at 1000 °C for 3 hours, which was beneficial to removing organic substances such as ethyl cellulose and starch in the composite cathode and anode and creating a porous morphology for the cathode and anode. As shown in Figure 2 (a), the cross-sectional SEM image of the membrane reactor shows that the porous electrode is tightly combined with the dense electrolyte, and the porous microstructure is beneficial to gas diffusion and increases the contact area between the reaction gas and the membrane; Figure 2 (b) is the local enlarged SEM image of the electrode, showing that SDC nanoparticles are evenly distributed on the electrode surface, effectively expanding the three-phase boundary of the reaction.Figure 2 (c) is the particle size statistical chart of SDC particles, and the average particle size of the particles is about 32.25 nm.
[0064] (6) Then, a current collector layer (silver paste) is coated on both electrode layers, and silver wires (with a diameter of 0.2 mm) are adhered to both sides of the composite cathode and the composite anode as leads. After drying in an oven, a membrane reactor for oxygen-argon separation is obtained. Example 2
[0065] A method for separating pure oxygen from air based on a flat solid oxide cation conductor membrane reactor.
[0066] In this example, the membrane reactor is prepared by the same method as in Example 1. The difference is that after the membrane reactor is prepared, it is fixed on a self-made membrane reactor carrier device for testing. The specific testing process is as follows: (1) Fix the membrane reactor on a self-made device with high-temperature ceramic glue, and wait for it to cure before putting it into a tube furnace for heating.
[0067] (2) When the test temperature is reached, air with a flow rate of 50 mL / min is introduced on the feed side, and helium with a flow rate of 50 mL / min is introduced on the purge side. An external voltage of 1.2 V is applied with an electrochemical workstation.
[0068] (3) Connect the tail gas on the purge side to a gas chromatograph, and collect the oxygen permeation amount of the membrane reactor at a voltage of 1.2 V. Figure 4 It shows that for the BSCF-SDC / LSGM / BSCF-SDC membrane reactor at a voltage of 1.2 V, the Faraday efficiency is always close to 100%, and the oxygen permeation amount increases with the increase of temperature. The oxygen permeation amount reaches 129.8 mol h -1 m -2 . Example 3
[0069] A method for oxygen-argon separation based on a solid oxide BSCF-SDC / LSGM / BSCF-SDC membrane reactor.
[0070] In this example, the membrane reactor is prepared by the same method as in Example 1, and the testing method is the same as in Example 2. The difference is that the gas introduced into the feed side of the membrane reactor is an oxygen-argon mixture. Specifically as follows: (1) Fix the membrane reactor on a self-made device with high-temperature ceramic glue, and wait for it to cure before putting it into a tube furnace for heating.
[0071] (2) When the test temperature is reached, an oxygen-argon mixture with a flow rate of 3 mL / min is introduced on the feed side, where the oxygen concentration is 0.5%. Helium with a flow rate of 50 mL / min is introduced on the purge side. An external voltage of 1.2 V is applied with an electrochemical workstation and the current is recorded.
[0072] (3) Connect the tail gas on the purging side to a gas chromatograph and collect the oxygen permeation amount of the membrane reactor at a voltage of 1.2 V. Figure 5 (a) shows the current density and Faraday efficiency of the BSCF-SDC / LSGM / BSCF-SDC membrane reactor at a voltage of 1.2 V, Figure 5 (b) shows the oxygen permeation amount of the membrane reactor and the purification degree of argon. From 600 - 800 °C, the oxygen permeation amount increases with the increase of temperature, and the purity of argon increases from 99.93% to 99.9998%. Comparative Example 1
[0073] A preparation method of a solid oxide BSCF / LSGM / BSCF membrane reactor.
[0074] The membrane reactor in this comparative example is prepared by the same method as in Example 1, except that the cathode and anode materials BSCF of the membrane reactor are no longer compounded with SDC. The specific steps are as follows: (1) Press the solid-phase synthesized La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) precursor powder into a disk using a tablet press and heat-treat it at 1500 °C for 10 hours to prepare a dense electrolyte with a thickness of about 400 microns, which serves as the support and electrolyte of the membrane reactor.
[0075] (2) Prepare Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) powder by the sol-gel method. Its XRD pattern is as shown in Figure 1 (c). The characteristic peaks of BSCF are consistent at various temperatures, but from the enlarged view of the main peak in Figure 1 (d), it can be seen that the peak position of BSCF moves towards a lower angle with the increase of temperature, and the trend is obvious, indicating that the lattice of BSCF gradually expands with the increase of temperature.
[0076] (3) Add 20% ethyl cellulose, 5% starch and an appropriate amount of turpentine alcohol (2 - 4 mL of turpentine alcohol is added per 1 g of BSCF mass) to the BSCF powder, and mix and ball-mill for 30 hours to make a pure BSCF electrode paste.
[0077] (4) Coat the pure BSCF paste on both sides of the electrolyte as the composite cathode and anode of the membrane reactor.
[0078] (5) After the pure BSCF slurry is completely coated, it is heat-treated at 1000 °C in air for 3 hours, which is beneficial to remove organic substances such as ethyl cellulose and starch in the composite cathode and anode, and to create a porous morphology of the cathode and anode. As Figure 3 (a) is the cross-sectional SEM image of the membrane reactor. The porous electrode and the dense electrolyte are split from each other, which is attributed to the fact that the thermal expansion coefficient of BSCF is much larger than that of the electrolyte LSGM, resulting in a low matching degree between the two. Figure 3 (b) is the partially enlarged SEM image of the electrode. The figure shows that the boundary of the pure BSCF electrode is clear, the surface is smooth and there are no particles attached.
[0079] (6) Then, a current collector layer (silver paste) is coated on both electrode layers, and silver wires (with a diameter of 0.2 mm) are adhered to both sides of the composite cathode and the composite anode as wires. After drying in an oven, a membrane reactor for oxygen-argon separation can be obtained. Comparative Example 2
[0080] A solid oxide BSCF / LSGM / BSCF membrane reactor for separating pure oxygen from air.
[0081] In this comparative example, the membrane reactor is prepared by the same method as in Comparative Example 1, except that after the membrane reactor is prepared, it is fixed on a self-made device for testing. The specific testing process is as follows: (1) Fix the membrane reactor on a self-made device with high-temperature ceramic glue, and wait for it to cure before putting it into a tube furnace for heating.
[0082] (2) When the temperature rises to the test temperature, air with a flow rate of 50 mL / min is introduced on the feed side, and helium with a flow rate of 50 mL / min is introduced on the purge side. An external voltage of 1.2 V is applied with an electrochemical workstation.
[0083] (3) Connect the tail gas on the purge side to a gas chromatograph, and collect the oxygen permeation amount of the membrane reactor at a voltage of 1.2 V. Figure 4 It shows that for the BSCF / LSGM / BSCF membrane reactor at a voltage of 1.2 V, the oxygen permeation amount increases with the increase of temperature, but is significantly lower than that of the BSCF-SDC / LSGM / BSCF-SDC membrane reactor under the same conditions. The oxygen permeation amount at 800 °C is only 29.5 mol h -1 m -2 , and its Faraday efficiency gradually decreases with the increase of temperature to 70%. Comparative Example 3
[0084] A tubular oxygen ion conductor membrane reactor for separating oxygen and argon, BCFN-GDC / GDC / BCFN-GDC; The principle of separating oxygen and argon by the membrane reactor in this comparative example is the same as that in Example 3, except for the preparation method, configuration, material selection of the membrane reactor, and the degree of argon purification. And the membrane reactor uses fractional purification.
[0085] (1) Prepare a Ce 0.1 Gd 0.9 O 2-x (GDC) membrane by the casting method and sinter it in air at 1450 °C for 10 hours to obtain a dense GDC membrane.
[0086] (2) Coat both the inner and outer sides of the GDC membrane with a Ba 0.9 Co 0.7 Fe 0.3 Nb 0.1 O 3-x - GDC (BCFN) catalyst, and after sintering, obtain a sandwich-structured tubular membrane reactor.
[0087] (3) Coat the current collector layer and attach wires to obtain a complete tubular membrane reactor for standby. Compared with the flat plate membrane reactor, the tubular membrane reactor has a longer current collection path, which easily leads to a lower power density.
[0088] (4) Pass an oxygen-argon mixture with a flow rate of 50 mL min -1 and an oxygen concentration of 50% into the feed side of the membrane reactor, and after 8 times of fractional purification, finally obtain argon with a purity ≥ 99.99%.
[0089] This preparation method is more complex and cumbersome compared with the tablet pressing and sintering method of the flat plate type. In addition, Ce 4+ in the GDC membrane is unstable at high temperatures and is easily valence-changed to Ce 3+ to form electronic conductivity, ultimately causing a short circuit inside the membrane reactor. And under the same conditions, the conductivity of GDC is slightly lower than that of the LSGM membrane in Example 3.
[0090] For the argon purified by this membrane reactor, the oxygen impurity concentration ≤ 100 ppm, and the oxygen concentration is relatively high, which is not suitable for many high-purity argon application fields. In contrast, for the argon prepared in Example 3, its oxygen content ≤ 10 ppm, which is applicable in fields such as semiconductor manufacturing, metal smelting, photovoltaic materials, and lighting.
[0091] In summary, the flat plate solid oxide oxygen ion conductor membrane reactor provided by the present invention, as well as the preparation method of the flat plate solid oxide oxygen ion conductor membrane reactor, the oxygen-argon separation method using the flat plate solid oxide oxygen ion conductor membrane reactor, and the application of the flat plate solid oxide oxygen ion conductor membrane reactor can improve the oxygen ion conductivity, improve the stability of the membrane reactor, and can deeply separate argon and oxygen to prepare high-purity argon.
[0092] The above embodiments are only preferred exemplary embodiments of the present application, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any person skilled in the art within the technical scope disclosed by the present invention can easily think of development or replacement, which all fall within the protection scope and the disclosure scope of the present invention.
Claims
1. A flat-plate solid oxide oxygen ion conductor membrane reactor, characterized in that: The flat-plate solid oxide oxygen ion conductor membrane reactor comprises an anode and a cathode, as well as a wire and a power source, wherein the anode and the cathode are connected to the power source via the wire; The anode and cathode include a support, and cathode and anode coatings on both sides of the support, the support is an LSGM sheet, and the coating is a layer formed by coating of BSCF-SDC slurry; The LSGM is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ ; The BSCF is Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ ; SDC is Ce 0.8 Sm 0.2 O 2-δ ; The BSCF-SDC is a material obtained by composite calcination of BSCF and SDC.
2. A flat-plate solid oxide oxygen ion conductor membrane reactor according to claim 1, characterized in that: The conductive wire is a silver wire.
3. A method for preparing a flat-plate solid oxide oxygen ion conductor membrane reactor according to any one of claims 1 to 2, characterized in that: The steps include: (1) The LSGM precursor powder is formed into flakes and heat treated at 1400-1500 °C to serve as the support and electrolyte of the membrane reactor; (2) BSCF and SDC are mixed and sintered in a mass ratio of 3:1-1:1, and after sintering, 10-20% of ethyl cellulose and 3-5% of starch and turpentine alcohol accounting for the total mass of BSCF-SDC are added, and the mixture is ball-milled to prepare BSCF-SDC slurry; (3) coating the BSCF-SDC slurry obtained in step (2) on both sides of the LSGM support as the composite cathode and anode of the membrane reactor; (4) After the BSCF-SDC slurry is coated, it is heat treated at 900-1200 °C; silver paste is applied to the surface of the anode and cathode, and then the wire is glued to the surface of the silver paste to obtain a membrane reactor for separating trace oxygen in argon; The LSGM is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ ; The BSCF is Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ ; SDC is Ce 0.8 Sm 0.2 O 2-δ ; The BSCF-SDC is a material obtained by composite calcination of BSCF and SDC.
4. The method for preparing a flat-plate solid oxide oxygen ion conductor membrane reactor according to claim 3, characterized in that: The heat treatment time at 1400-1500° C. in step (1) is 8-20 hours, preferably 10-15 hours.
5. A method for preparing a flat-plate solid oxide oxygen ion conductor membrane reactor according to any one of claims 3 to 4, characterized in that: In step (4), the heat treatment time at 900-1200° C. is 1-20 hours, preferably 2-10 hours, and preferably 2-6 hours.
6. A method for preparing a flat-plate solid oxide oxygen ion conductor membrane reactor according to claim 3-4, characterized in that: The LSGM is prepared by the following method: (a) La2O3, SrCO3, Ga2O3 and MgO are weighed according to the stoichiometric ratio, and ball-milled evenly for 10-50 hours, preferably 20-30 hours; ethanol or acetone is added during the ball-milling process, and the ratio of the total amount of La2O3, SrCO3, Ga2O3 and MgO to the organic solvent is 1 g: 0.5-2 mL, preferably 1 g: 0.5-1.5 mL; (b) drying the uniformly ball-milled powder and calcining it at 800-1200° C. for 4-12 hours, preferably at 900-1000° C. for 6-8 hours, to obtain LSGM precursor powder; (c) The LSGM precursor powder is pressed into a disc and heat-treated at 1400-1500 °C for 8-20 hours, preferably 10-15 hours, to serve as a support and electrolyte for a membrane reactor.
7. A method for separating oxygen and argon using a flat-plate solid oxide oxygen ion conductor membrane reactor according to claim 1-2, characterized in that: The membrane reactor is fixed in a mold, and at a temperature of 750-900°C, an argon-oxygen mixed gas is introduced into the cathode side of the membrane reactor, and helium is introduced into the anode side for purging; an electrolysis voltage of 1-2.0V, preferably 1.2-1.5V, is applied between the composite anode and the composite cathode.
8. The oxygen-argon separation method according to claim 7, characterized in that: An oxygen-argon mixed gas is introduced into the cathode side of the membrane reactor, and the oxygen concentration is 0.1-5%; preferably, the oxygen concentration is 0.5-1%; The cathode of the membrane reactor is fed with an oxygen-argon mixed gas at a flow rate of 3-10 mL / min, preferably 3-5 mL / min; The anode of the membrane reactor is fed with nitrogen or helium at a flow rate of 40-80 mL / min, preferably 50-60 mL / min.
9. The oxygen-argon separation method according to claim 8, characterized in that: The oxygen concentration of the purified argon gas is lower than 10 ppm.
10. An application of a flat-plate solid oxide oxygen ion conductor membrane reactor according to claim 1-2, characterized in that: The invention is used for the application in oxygen-argon separation, and the oxygen concentration of the argon gas is lower than 10 ppm after being purified.
Citation Information
Patent Citations
Non-metal anion doped LAMOX type oxygen ion conductor oxygen permeation membrane material as well as preparation method and application thereof
CN112694329A
Ceramic oxygen pump with symmetrical metal supporting bodies and preparation method of ceramic oxygen pump
CN115863719A
High permeability membrane for oxygen separation and fabrication method thereof
KR1020160117900A
High permeability oxygen separation membrane coated with electroactive layer on both sides and fabrication method thereof
US20170005341A1
Inert gas purifying system
US5454923A